Village fund management accountability in efforts to reduce stunting in Pantai Labu Sub-district - Yusri Yusri; Chairina Chairina (Jurnal Mantik, 2024)
This study aims to examine the accountability of village fund management in reducing stunting. Stunting is still a common health problem in various regions, especially in rural areas. Village funds are an important source of financing for health and nutrition programs at the village level. Therefore, it is important to understand the extent to which village fund management contributes to stunting reduction efforts. This research methodology used secondary data analysis and interviews with stakeholders at the village level. The results showed that accountability in village fund management plays an important role in stunting reduction efforts. Factors such as transparency, community participation, and effective oversight have a great impact on ensuring that village funds are used efficiently for nutrition and health programs. However, the study also identified several barriers to achieving the desired level of accountability. For example, a lack of community understanding and awareness of village funds, as well as weaknesses in reporting and monitoring systems. Therefore, further efforts are needed to improve the accountability of village fund management, including community education and improved monitoring mechanisms. The results of this study provided valuable input for the government and other stakeholders in their efforts to address stunting at the village level. Accountability in village fund management can be a key factor in ensuring that available resources are used effectively and sustainably to improve child nutrition in rural areas.